Análise do uso das águas de uma empresa do ramo petroquímico via análise de sobrevivência - Novaes, Edimar Izidoro [UNESP] (2014)
In literature the use of planarians as bioindicators of water quality is discussed, because differently from classic toxicology tests, the animals are able to capture long term exposition effects. Currently, one of techniques to verify the water quality with the use of planarians is performing the comet assay. We propose a new alternative to verify the water quality by accompany lifetime planarians on different aquatic environments. In the present study we used data obtained from a petrochemical company that uses Jaguari river on its production process. Survival Analysis was used to compare the levels of toxic pollutants on different aquatic environments. We also propose a regression model to make inference in the lifetimes of planarians for the different locations from which water samples were collected. The new proposed method presented an efficient and low cost way to use planarians of Dugesia Tigrina specie as water quality bioindicators